2005
DOI: 10.1128/mcb.25.21.9478-9490.2005
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation of the pH-Responsive Rim101 Pathway in Yeast Mutants Defective in Late Steps of the MVB/ESCRT Pathway

Abstract: In many fungi, transcriptional responses to alkaline pH are mediated by conserved signal transduction machinery. In the homologous system in Saccharomyces cerevisiae, the zinc-finger transcription factor Rim101 is activated under alkaline conditions to regulate transcription of target genes. The activation of Rim101 is exerted through proteolytic processing of its C-terminal inhibitory domain. Regulated processing of Rim101 requires several proteins, including the calpain-like protease Rim13/Cpl1, a putative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
99
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(115 citation statements)
references
References 81 publications
(101 reference statements)
14
99
1
1
Order By: Relevance
“…Third, we show here that the functions of Dfg16, Rim8, Rim9, and Rim21 may be bypassed by a vps4 defect, whereas the function of Rim13 cannot. A recent independent study reported completely convergent findings (Hayashi et al, 2005). Finally, the fact that Rim13 and Rim101 are not required for Rim20 focus formation is consistent with the proposal that Rim20 functions by recruiting both Rim13 and Rim101, if one assumes that a Rim20 focus serves as a recruitment site.…”
Section: Rim20 Foci and Rim101 Processing Activitysupporting
confidence: 72%
See 2 more Smart Citations
“…Third, we show here that the functions of Dfg16, Rim8, Rim9, and Rim21 may be bypassed by a vps4 defect, whereas the function of Rim13 cannot. A recent independent study reported completely convergent findings (Hayashi et al, 2005). Finally, the fact that Rim13 and Rim101 are not required for Rim20 focus formation is consistent with the proposal that Rim20 functions by recruiting both Rim13 and Rim101, if one assumes that a Rim20 focus serves as a recruitment site.…”
Section: Rim20 Foci and Rim101 Processing Activitysupporting
confidence: 72%
“…On the other hand, mutants defective in Vps4 or in Vps2 and Vps24, the ESCRT-III subunits that recruit Vps4, were capable of producing cleaved Rim101 (Xu et al, 2004). Largely consistent results have been obtained independently for S. cerevisiae (Barwell et al, 2005;Hayashi et al, 2005;Rothfels et al, 2005) and other fungi (Kullas et al, 2004;Xu et al, 2004;Cornet et al, 2005). These findings led to the proposal that vesicle-associated Snf7 is required for productive interaction with Rim20, leading to Rim101 cleavage (Xu et al, 2004).…”
supporting
confidence: 61%
See 1 more Smart Citation
“…In the pH-responsive pathway, Rim13, Rim20, and Rim21 are all located upstream of the transcription factor Rim101 (Hayashi et al, 2005;Boysen and Mitchell, 2006). Rim21 and Dfg16, both multimembrane-spanning proteins, and their homologues are thought to serve as pH sensors (Peñ alva and Arst, 2004; Barwell et al, 2005;Herranz et al, 2005;Boysen and Mitchell, 2006).…”
Section: The Rim101 Pathway Is Involved In the Induction Of Rsb1mentioning
confidence: 99%
“…The pFI1 plasmid (Hayashi et al, 2005), which encodes N-terminally triple HA-tagged Rim101 (HA-Rim101), was a kind gift from Dr. Tatsuya Maeda (Tokyo University, Japan). The pIKD412 plasmid, which is derived from the pRS423 vector (2 , HIS3 marker) (Christianson et al, 1992), encodes RSB1-HA under the control of the RSB1 promoter (P RSB1 ).…”
Section: Plasmidsmentioning
confidence: 99%